Advanced Manufacturing and Materials Science Selected Extended Papers of ICAMMS 2018 (Lecture Notes on Multidisciplinary Industrial Engineering,, 2018)
This book presents selected papers from the international conference on advanced manufacturing and materials sciences (ICAMMS 2018). The papers reflect recent advances in manufacturing sector focusing on process optimization and give emphasis to testing and evaluation of new materials with potential use in industrial applications.